Model Pembelajaran dan Implementasi Pendidikan HAM Dalam Perspektif Pendidikan Islam dan Nasional - Siti Julaeha; Mohamad Erihadiana (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
The importance of determining a learning model to achieve a goal that will be achieved optimally, the learning model is a guide for every teacher, with the right learning model, the achievement of the expected results is in accordance with what is planned, in the learning model and implementation of human rights education In the perspective of Islamic and national education, this concept has implications for at least three things. First, the right learning model to be used in the implementation of human rights education. Second, the implementation of human rights education in the perspective of Islamic education, and third, the implementation of human rights education in the perspective of national education. Thus, the implementation of human rights education in the perspective of Islamic and national education is interconnected, so that all three synergize towards the formation of students who have ibadurrohman and moral character. ul karimah